Principles of Accounting–Introductory (Book). - Mehl, Arthur G.; Zeff, Stephen A. (The Accounting Review, 1964)
Reviews the book "Principles of Accounting–Introductory," 6th ed., by H.A. Finney and Herbert E. Miller.